Very late-onset lead-associated endocarditis - Min-Soo Cho; Sung-Hwan Kim; Gi-Byoung Nam; Kee-Joon Choi; You-Ho Kim (Canadian Journal of Infectious Diseases and Medical Microbiology)
Lead-associated endocarditis is a serious complication due to device implantation. The present article reports on a case involving a 57-year-old man with microbiologically and pathologically confirmed lead-associated endocarditis caused by Staphylococcus capitis. Transesophageal echocardiography is essential for diagnosis, and treatment usually requires appropriate antibiotics and removal of the lead.